Love Is Blind! Exploring the Impact of Brand Love on eWOM in Chinese Hospitality Industry - Bilal, Muhammad; Akram, Umair; Zhang, Yunfeng; Cai, Shukai; Wang, Zhuliang (Frontiers in Psychology, 2022)
The rising penetration and value of online information reviews in the hospitality industry have been extensively examined. People are increasingly interacting on interactive online media, prompting firms to create online communities to share eWOM with them and with one another in order to increase brand love. This study seeks to discover what drives consumers to participate in these online brand communities. To examine the research model, an online survey was conducted on 508 consumers who had shared eWOM on SNS. Structural equational modeling (SEM) was employed to test all hypotheses. The findings show that each of the variables has a high impact on brand love, with information quality and virtual interaction having the greatest impact. As a result of brand love, eWOM is significantly increased. Additionally, findings show that the gender gap in the online setting is increasing, as the influence of all characteristics then reward of online brand communities on brand love was adaptable among both male and female associates. Considering the effects of online features (information quality, system quality, virtual interaction, and reward) of online brand communities' impact on brand love and eWOM. Online hotels manager is advised to carefully develop their marketing strategies to retain and attract new consumers. Furthermore, online hotels manager can use the findings from this study to understand the consequences when eWOM is strongly influenced by online brand communities' features. This study is one of the first to illustrate and empirically confirm insight into how online features influence brand lovers in online brand communities. The study adds to the body of knowledge concerning the effectiveness of social media marketing in the Chinese hotel sector.